Impact of guaiacol on the formation of undesired macromolecules during catalytic hydroconversion of bio-oil: A model compounds study. (December 2016) - Ozagac, M.; Bertino-Ghera, C.; Uzio, D.; Rivallan, M.; Laurenti, D.; Geantet, C.
Abstract: Although catalytic hydroconversion of pyrolysis bio-oils has been studied for many years, side reactions such as condensation or oligomerization leading to high molecular weight compounds still need comprehensive studies. In this work, the catalytic hydroconversion of D-glucose, furfural, acetic acid and guaiacol representative of pyrolysis bio-oils was investigated separately before testing a 5-component mixture. Thanks to a detailed analytical strategy (i.e. SEC, 13 C NMR, GC, HPLC), this paper focuses on the effect of guaiacol conversion on sugar-like macromolecules. The study of single D-glucose and furfural revealed the fast production of high molecular weight compounds (up to 700 g mol −1 ) that were proven to further precipitate (from D-glucose). Guaiacol addition led to a decrease of the solid production through solubilizing and/or reacting with macromolecules. This phenomenon produced larger soluble macromolecules (up to 5000 g mol −1 ). Results show that guaiacol and its hydroconversion products formed soluble macromolecules at short reaction times and low temperatures. Graphical abstract: Highlights: Catalytic hydroconversion of bio-oil model compounds mixtures has been performed. Effect of Guaiacol has been investigated. Guaiacol limits the solid precipitation from D-glucose and furfural products. Macromolecule solubilization in the organic phase was evidenced.